Asynchronous Circuit Applications - Di, Jia; Smith, Scott C. (Materials, circuits and devices series ;, 2019)
The book consists of 16 chapters and covers the following topics: asynchronous circuits; power-performance balancing; ultra-low supply voltages; analog electronics; asynchronous sensing; high-speed circuits; network-on-chips; field-programmable gate arrays; extreme temperatures; radiation hardness; logic design; clock distribution networks; NCL design tools and formal verification.